Evaluation of weed competitiveness of direct-seeded rice (Oryza sativa) genotypes under different weed management practices - KUMAR, RAKESH; MISHRA, J S; KUMAR, SANTOSH; RAO, K K; HANS, HANSRAJ; BHATT, B P; SRIVASTAVA, A K; SINGH, SUDHANSHU (The Indian Journal of Agricultural Sciences, 2020)
Performance of eight rice (Oryza sativa L.) genotypes (‘Swarna Shreya’, ‘IR84899-B-179-13-1-1-1’,‘IR83929-BB- 291-2-1-1-2’,‘DRR-42’,‘IR84899-B-183-20-1-1-1’,‘IR84894-143-CRA-17-1’,‘DRR-44’,‘Rajendra Bhagwati’) was evaluated in three weed management practices, i.e. application of pendimethalin @1.0 kg/ha as pre-emergence (PE) at 2 days after sowing (DAS) followed by (fb) bispyribac-Na @30 g/ha as post-emergence (POE) at 20 DAS and two hand weedings (40 and 60 DAS)-low weed pressure; application of pendimethalin @ 1.0 kg/ha as PE fb bispyribac- Na @ 30 g/ha as POE at 20 DAS-medium weed pressure and pendimethalin @ 1.0 kg/ha alone-high weed pressure during rainy seasons of 2016 and 2017 at Patna, Bihar. Application of pendimethalin (PE) followed by bispyribac-Na (POE) and two hand weedings (low weed pressure) significantly reduced weed infestation compared to pendimethalin alone (medium weed pressure). Markedly lower weed density was recorded with ‘IR84899-B-179-13-1-1-1’. Low weed pressure produced 90 and 26% more grain yield (2.53 t/ha) compared to medium (2.01 t/ha) and high weed pressure (1.33 t/ha).Significantly higher grain yield was recorded with ‘IR84899-B-179-13-1-1-1’ (2.32 t/ha) followed by ‘Swarna Shreya’ (2.18 t/ha). Low weed pressure had significantly higher gross returns (45.9×103 `/ha) and net returns (14.1×103 `/ha). Amongst genotypes, ‘IR84899-B-179-13-1-1-1’ had the highest gross returns (44×103 `/ha) and net income (17.6×103 `/ha). Hence, it may be concluded that application of pendimethalin (PE) fb bispyribac-Na (POE) along with hand weeding had significant impact on reduction of weed infestation and helps in achieving the higher grain yield of direct-seeded rice genotypes in eastern India.